Accuracy of 2D CT-Based Measurements of Rotational Alignment of the Femoral Component for Total Knee Arthroplasty - Park, Jun Young; Kwon, Hyuck Min; Cho, Byung Woo; Lee, Woo-Suk; Yang, Ick Hwan; Park, Kwan Kyu (Yonsei medical journal, 2021)
We aimed to investigate the accuracy of two-dimensional computed tomography (2D-CT)-based methods for measuring rotational alignment of the femoral component during total knee arthroplasty in comparison to reference values for three-dimensional (3D) reconstruction. We selected the "most protruding transepicondylar axis section," "most protruding posterior condylar line section," and "distal femoral cut section" on 2D-CT images for 100 knees. We investigated posterior condylar angle (PCA) and condylar twist angle (CTA) values using three different methods on 2D-CT and compared to these values to those obtained using a 3D model. The mean PCA and CTA values were 2.8° and 7.0° on the 3D model and 2.0° to 2.1° and 5.9° to 6.0° on 2D-CT, respectively. Errors in PCA and CTA measurement included internal rotation of 0.8° and 1.1° with the 1-plane and 2-plane methods and 0.9° and 1.0° with the assumed resection method, respectively. Mean errors in PCA and CTA values measured using three different methods on 2D-CT were not significantly different. However, PCA and CTA values measured on 2D-CT were approximately 1° smaller than their 3D values. Thus, we suggest that adding 1° to the mean PCA and CTA values obtained from a single plane of 2D-CT would provide values similar to those obtained from 3D reconstruction.